2019
DOI: 10.14406/acu.2019.012
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Fire Needling Treatment for Knee Osteoarthritis: Focused on Comparative Studies with Manual Acupuncture Treatment during Recent Five Years

Abstract: The purpose of this study is to review the effectiveness of fire needling treatment for knee osteoarthritis in comparison with manual acupuncture treatment. Methods : Through four foreign online databases (PubMed, Cochrane library, EMBASE, and CNKI) and five domestic online databases (NDSL, RISS, KISS, OASIS, and KTKP), we searched for clinical studies that performed fire needling treatment for knee osteoarthritis until May 10, 2019. Only randomized controlled trials were selected and we assessed the risk of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In traditional Korean medicine (which is a representative conservative treatment), various treatments such as moxibustion, acupuncture, pharmacopuncture, and herbal medicine are used to treat osteoarthritis. In Korea, fire needling treatment of osteoarthritis, and Bee venom treatment of osteoarthritis have been reported [6,7]. However, there are no systematic reviews or meta-analyses of moxibustion treatment of osteoarthritis in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…In traditional Korean medicine (which is a representative conservative treatment), various treatments such as moxibustion, acupuncture, pharmacopuncture, and herbal medicine are used to treat osteoarthritis. In Korea, fire needling treatment of osteoarthritis, and Bee venom treatment of osteoarthritis have been reported [6,7]. However, there are no systematic reviews or meta-analyses of moxibustion treatment of osteoarthritis in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…[92,94] While 24 of the 65 included studies reported on the safety of interventions, there was no report of safety related to FA and only 1 study related to ACE, which ranked high in our network meta-analyses. FA is used to treat lateral epicondylitis, [95] knee osteoarthritis, [96] and ankle sprain, [97] and may cause pain, burns, and skin rash due to a red-hot needle. There were few reports of adverse events to the FA in the previous studies, [95][96][97] and Yeon et al [98] reported that after FA, local third-degree burns were observed in the muscle and skin layers without any scarring, and the residual products present after FA did not exert toxicity, but rather increased cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…FA is used to treat lateral epicondylitis, [95] knee osteoarthritis, [96] and ankle sprain, [97] and may cause pain, burns, and skin rash due to a red-hot needle. There were few reports of adverse events to the FA in the previous studies, [95][96][97] and Yeon et al [98] reported that after FA, local third-degree burns were observed in the muscle and skin layers without any scarring, and the residual products present after FA did not exert toxicity, but rather increased cell growth. ACE has been used for the treatment of musculoskeletal pain, obesity, and facial palsy in Korea, China, and Taiwan.…”
Section: Discussionmentioning
confidence: 99%